The Commonwealth as a force for good - Segal, Hugh (2012)
Stresses the need for urgent and sustained action on the recommendations of the Eminent Persons Group if the full potential of the association of nations is to be realised. Argues that unless the focus on human rights, democracy and the rule of law is maintained, the organisation may be unable to maintain its reputation as a compelling force for good.